Deprescribing in advanced illness. (2nd September 2016) - Akinbolade, Olusola; Husband, Andy; Forrest, Simon; Todd, Adam
Abstract : Patients with advanced illness such as cancer, chronic obstructive pulmonary disease, and Parkinson's disease experience acute symptoms and are usually prescribed medications to manage these, alongside drugs to treat other co-morbid, long-term conditions. As such, the pharmacotherapeutic burden for these patients is high and polypharmacy is common. Previous studies have revealed the prevalence of potentially inappropriate prescribing within this group of patients, and identified the need for attention to 'deprescribing'. Deprescribing can be defined as a process of optimization of medication regimens through cessation of potentially inappropriate or unnecessary medications. Patients usually have reservations about taking medications and may be willing to discontinue one or more medications considered 'inappropriate'. Similarly, healthcare professionals experience some challenges discussing deprescribing approaches to patients with advanced illness. This article reviews research on prescribing medicines to patients with advanced illness, focusing on the identification of the prevalence of inappropriate or unnecessary medicines to the initiation of the deprescribing process. The review demonstrates the paramount importance of further research exploring the perspective of healthcare professionals and patients on the subject of deprescribing to facilitate its further acceptance in practice.